The legacy of Bristol: public disclosure of individual surgeons' results. Issue 7463 (19th August 2004) - Keogh, Bruce; Spiegelhalter, David; Bailey, Alan; Roxburgh, James; Magee, Patrick; Hilton, Colin
Abstract : Measurement of outcomes from medical or surgical interventions is part of good practice, but publication of individual doctors' results remains controversial. The authors discuss this issue in the context of cardiothoracic surgery